Active Transformer Flux Balancing for a PSFB-DAB Converter - Axelsson, Philip; Nabi Pour, Awaz (My University, 2025)
Abstract This thesis investigates the implementation of active flux balancing on a planar transformer within a PSFB-DAB converter system. This is used to mitigate magnetizing flux and prevent transformer core saturation. The approach starts with the creation of a state-space model of the transformer, followed by the development of two PI-based controllers including a flux balancing controller and a DC offset controller. A hybrid control approach was also briefly investigated. The worst-case operating scenario for the system was examined considering component variations, temperature effects, changes in primary and secondary voltages and phase shifts. This was then used to evaluate the worst-case operating conditions to determine the maximum offset the controller could handle while still preventing saturation. The results show that the converter can handle a maximum voltage step of 4.9 V for the worst case operating condition of, Vp = 850, Vs = 550 and φ = −90◦
Keywords: Keywords: Planar transformer, PSFB-DAB, DAB, Active flux balancing, current control, control system, PI-control, DC-DC application, state-space, PWM